2010
DOI: 10.1021/ie100308f
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Fischer−Tropsch Catalysts Using Nickel Promoter as a Rhenium Substitute to Suppress Deactivation

Abstract: Catalysts with cobalt as the Fischer-Tropsch (FT) metal and nickel and/or rhenium as promoters on alumina of different pore sizes, a stabilized alumina, silica, or titania as supports were investigated for activity, selectivity, and deactivation up to 800 h of operation in a fixed-bed reactor. From the observed selectivities, there is no indication that nickel as a promoter with a loading up to 5 wt % influences the selectivities to higher hydrocarbons for low-temperature (<250 °C) cobalt FT synthesis. Nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
7
37
0
Order By: Relevance
“…We have previously compared the reduction profiles of a 20 wt% Co on c-alumina catalyst with and without Re or Ni as promoter by the latter method [24]. It was clearly demonstrated that both promoters facilitate the final reduction step of CoO to Co metal.…”
Section: Characterization Of Attrition Resistant Catalystsmentioning
confidence: 97%
“…We have previously compared the reduction profiles of a 20 wt% Co on c-alumina catalyst with and without Re or Ni as promoter by the latter method [24]. It was clearly demonstrated that both promoters facilitate the final reduction step of CoO to Co metal.…”
Section: Characterization Of Attrition Resistant Catalystsmentioning
confidence: 97%
“…They systematically studied the support effect of bimetallic Co-Ni catalyst and succeeded in the preparation of Co-Ni catalyst showing high activity and selectivity to gasoline-range hydrocarbons (C 5 -C 12 ). It was also reported that Ni was effective as the reduction promoter of supported Co catalysts such as Co/SiO 2 [44], Co/Al 2 O 3 [45], Co/HZSM-5 [46] and Co/CNT [47]. Although various attempts have been made to prepare highly active bimetallic Co-Ni catalyst for FT synthesis, factors influencing the activity of Co-Ni catalyst are not fully understood yet.…”
Section: Introductionmentioning
confidence: 95%
“…The tendencies of the nickel (Ni) catalyst to generate high levels of CH 4 via methanation chemistry and form volatile carbonyls resulting in the continuous loss of metal at the FTS operating conditions made Ni unsuitable for the commercial FTS process (Dry, 2004a p. 533;Enger and Holmen, 2012). Recently, Rytter et al (2010) identified Ni as a suitable replacement for rhenium (Re) as a reduction and activity promoter to their Co catalyst in the FTS process. They reported the presence of Ni has a profound positive impact on the catalytic activity, as well as the start of run activity, steady-state level, and deactivation rate.…”
Section: Introductionmentioning
confidence: 98%